Agromet advisory services to mitigate the effect of adverse weather conditions and enhance farmers’ income - Ratiya, Puja Bhimabhai; Thakor, R F; Solanki, Aditi H (Indian Farming, 2022)
Agriculture sector is the foundation of the Indian economy. Weather variability plays a vital role in year-to-year fluctuation in agricultural production and productivity; both in rainfed as well as irrigated agriculture. In order to address this, India Meteorological Department (IMD) took initiative to issue block level Agromet Advisory Services (AAS) to farmers through District Agromet Unit (DAMU) established at KVKs. Agromet advisory service is the single window solution for all the queries related to fluctuating weather conditions and management in agricultural operations. The agromet advisory bulletins contain all possible risk mitigation measures for the major crops and livestock. Based on the weather forecast, a group of interdisciplinary and agromet scientists at DAMU prepared district and block level agromet advisory bulletins. These bulletins are sent to the farmers and other stakeholders of the corresponding district. The right weather information at the right time facilitates the farmers to plan agricultural operations from selection of crops to post harvest in order to avoid crop losses and ultimately increase farmers’ income.